Analysis of journalistic ethics in the media. La Posta case study - Aguiar, Nina Lulushca (2023)
This research focuses on the study of the native digital medium «La Posta» and its treatment of information. The objective is to analyze the application and adherence to ethical principles in journalism through a comprehensive review of its news articles. The methodological approach employed is content analysis, with a descriptive perspective; therefore, 31 informative journalistic articles from the «elTop» section, published on the official Instagram account of the medium in January 2023, were examined. The results of the analysis show that the medium does not conform to the ethical regulations of the Organic Law Reforming the Organic Communication Law (2019) of Ecuador. The news articles also do not adhere to the fundamental ethical principles of journalism. Additionally, the significance of advertising in the way the medium approaches information is highlighted. The absence of authorship in the analyzed content is evident, and there is a clear tendency to position the medium as the sole bearer of truth, without restrictions or limitations, with a prevailing private interest over social benefit.